Economic mechanisms to regulate environmental protection practices in industrial and household waste management in the Russian Federation (Nexo Revista Científica, 2021)
The study focuses on the aspects of environmental protection practices in the Russian Federation primarily with regard to industrial and household waste management. Waste now occupies significant areas and causes pollution of the adjacent territories and specifically underground waters that further mix with, and significantly spoil, ground waters. The study addresses the technologies of interaction and methods of economic stimulation to improve waste management going further both at the regional and national level. Almost no progress has been achieved in this direction in the Russian Federation over the past ten years – the main technological mechanism adopted in major cities and other major infrastructure facilities consisted in waste removal to a landfill without any specific treatment. More recently, urban and technological development has intensified environmental problems. The paper outlines waste management practices employed in Russia and other countries and provides an efficiency assessment. The basic economic mechanisms, such as tariff regulation, environmental levy and environmental impact fees, are described and assessed in terms of their stimulating effects on waste management improvement in the Russian Federation. Aspects of waste removal under a single regional operator are discussed and a model of public-private partnership in waste management is proposed and detailed.